Estimating Correlation Between Emotional Regulation and Independence in Early Childhood - Hastuti, Apriyani Puji; Ivana, Vanesya; Ispriantari, Aloysia; Soares, Domingos (Jurnal Ilmiah Kesehatan, 2025)
One of the aspects of childhood independence is managing emotional turmoil. Emotion regulation is an individual's style in determining what emotions they feel, when and how to describe them, and recognizing these emotions. This research estimates the correlation between emotional regulation and independence in early childhood. This research design used analytics with a cross-sectional approach. The population was 86 mothers with young children in the Ciptomulyo Malang Public Health Center (PHC) working area. There were 80 samples with a purposive sampling technique. The inclusion criteria were children living with their parents. The instrument for emotional regulation was the Emotional Regulation Questionnaire for Children and Adolescents (ERQ-CA), and for early childhood independence was the Child Independence Questionnaire. The results showed that parents had an authoritarian parenting style (85%). They had expressive suppression in emotion regulation (92.5%) and an independent category of early childhood independence (57.5%). The Spearman Rank test obtained p=0.002 (p<0.05) and the r=0.625. Thus, there was a significant correlation between emotion regulation and early childhood independence. In conclusion, emotion regulation affects early childhood independence. Further research could evaluate children's social and cultural context and individual characteristics, providing deeper insight into the factors influencing early childhood independence.